Hyperbaric oxygen therapy for nonhealing wounds: Treatment results of a single center. Issue 2 (30th December 2020) - Teguh, David N.; Bol Raap, René; Koole, Arne; Knippenberg, Bob; Smit, Casper; Oomen, Jan; van Hulst, Rob A.
Abstract: The present article evaluates the results of the treatment with adjuvant hyperbaric oxygen therapy (HBOT) of patients with nonhealing, chronic wounds. In the period 2013 to 2016, 248 patients were referred from various hospitals because of chronic wounds that were recalcitrant in healing despite standard wound care as described in national and international guidelines. After inclusion, all patients were treated with HBOT and subjected to a weekly standard wound care treatment. During each HBOT session, 100% O2 was administered for 75 minutes under increased pressure of 2.4 ATA. Wounds and quality of life were assessed before and after the total treatment period. A total of 248 patients have been evaluated. Diabetic foot ulcers were present in 134 patients, the remainder (114 patients) showed a variety of wound locations and etiologies. The number of HBOT treatments amounted to an average of 48 (range 20‐68) sessions. Before referral to our clinic, 31% of all wounds had existed for at least 18 months (72 patients). After HBOT, 81% of all wounds were near complete healing or completely healed, in 13% of the cases the wound was stable, and in 2% minor or major amputation had to be carried out. The mean treatment time for wounds pre‐existing fewer than 6 weeks ("early referrals") was 67 days, and 119 days for wounds pre‐existing more than 18 months ("late referrals"). A majority of the patients in our study referred with nonhealing wounds clinically improved when adjuvant HBOT was added to standard wound care protocols. No differences in success rate were seen between diabetic and nondiabetic wounds. It showed that HBOT is a well‐tolerated treatment.